2021
DOI: 10.1002/ece3.7382
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis shows that environmental DNA outperforms traditional surveys, but warrants better reporting standards

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 130 publications
(141 reference statements)
5
92
0
Order By: Relevance
“…Emerging DNA-based approaches have the potential to contribute towards evaluating river restoration success in several ways. DNA metabarcoding has repeatedly been shown to detect a greater number of species than traditional monitoring approaches such as kick-sampling and electrofishing [126]. Field, laboratory, and bioinformatic protocols to optimise the process are becoming better established for a range of taxa, from diatoms to fish and mammals.…”
Section: Dna-based Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging DNA-based approaches have the potential to contribute towards evaluating river restoration success in several ways. DNA metabarcoding has repeatedly been shown to detect a greater number of species than traditional monitoring approaches such as kick-sampling and electrofishing [126]. Field, laboratory, and bioinformatic protocols to optimise the process are becoming better established for a range of taxa, from diatoms to fish and mammals.…”
Section: Dna-based Approachesmentioning
confidence: 99%
“…Certain genes and transcripts have known ecological functions (e.g., cellulose degradation) and have been shown to respond with high specificity to particular stressors [127]. For example, the bacterial organophosphate hydrolase gene (opd) indicates pesticide degradation, whilst the ammonia monoxygenase gene (amoA) is activated during periods of intense organic matter breakdown [126]. New applications of these approaches from microbial ecology could be used to identify the main stressors on potential restoration sites and to monitor the status of those stressors at restored sites.…”
Section: Dna-based Approachesmentioning
confidence: 99%
“…The incorporation of species detection through bulk DNA obtained from environmental samples (environmental DNA, eDNA) is revolutionizing the way researchers monitor the marine biome (Bowers et al, 2021; Ficetola et al, 2008). By inferring species presence and absence indirectly through molecular approaches, eDNA surveys do not rely on visual observations, thereby simplifying species detection within inaccessible environments (Fediajevaite et al, 2021). In addition, the complexity of the DNA signal contained within environmental samples facilitates the detection of a broad range of taxonomic groups, and a larger number of individual species, than can be achieved using traditional monitoring (Jeunen et al, 2020; Kelly et al, 2017; Kim et al, 2019; Thomsen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that the amplification of DNA barcode regions from eDNA (i.e. eDNA metabarcoding) can be used to detect marine NNS [32][33][34][35] and that it is a sensitive and accurate method for biomonitoring [36,37]. However, eDNA surveys are rarely used in conjunction with existing methods to detect NNS range shifts, and eDNA metabarcoding can validate, endorse, or highlight flaws, in current biodiversity management strategies.…”
Section: Introductionmentioning
confidence: 99%